2001
DOI: 10.1054/bjoc.2001.1961
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor-I and prostate cancer: a meta-analysis

Abstract: Summary Some, but not all, epidemiological found have shown that high circulating levels of insulin-like growth factor-I (IGF-I) are associated with an increased risk of prostate cancer. We performed a meta-analysis on all the studies reported so far to evaluate this association. In our Medline search, 14 case-control studies were identified. A standard protocol abstracted information for each study. Hedges' standardized mean difference (HSMD) and odds ratio (OR) were used to estimate the effect of IGF-I and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(68 citation statements)
references
References 23 publications
4
64
0
Order By: Relevance
“…[4][5][6] A recent breast cancer study found 5 SNPs to be associated with elevated plasma levels of IGF1, 10 and 4 of those SNPs were positioned in the region of Block 3, as defined in our study. Interestingly one of those 4 SNPs was rs6220, whose minor allele is the final C allele in the TCC and CCC risk haplotypes (Table III).…”
Section: Discussionsupporting
confidence: 62%
“…[4][5][6] A recent breast cancer study found 5 SNPs to be associated with elevated plasma levels of IGF1, 10 and 4 of those SNPs were positioned in the region of Block 3, as defined in our study. Interestingly one of those 4 SNPs was rs6220, whose minor allele is the final C allele in the TCC and CCC risk haplotypes (Table III).…”
Section: Discussionsupporting
confidence: 62%
“…Additionally, expression of the protumor insulin-like growth factor (IGF)-1 is upregulated while expression of the anti-tumor IGF-1 binding protein (IGFBP)-3 is suppressed. [28][29][30] As pancreatic b-islet cell loss accelerates, insulin production declines, potentially yielding a protective effect later on. Thus, an alternative explanation for our null findings is that the REDUCE cohort is balanced with respect to diabetes progression and our results merely reflect cancelation of opposing risks.…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiologic studies have reported a positive association between circulating insulin-like growth factor-I concentration and prostate cancer risk (53)(54)(55)(56)(57). Furthermore, in a recent meta-analysis of studies examining the association of circulating insulin-like growth factor-I concentrations with prostate cancer risk, Shi et al found that insulin-like growth factor-I blood levels were higher in prostate cancer patients than in controls (58). Thus, during the early stage of abnormal glucose metabolism and development of type 2 diabetes mellitus (the insulinresistant step), prostate cancer risk may be increased due to increasing levels of insulin.…”
Section: Discussionmentioning
confidence: 99%